Sri Lanka : Promoting Agricultural and Rural Non-farm Sector Growth, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Economic development has brought about, the decline in contribution of the agricultural sector to the economy of Sri Lanka, and, consistent with this economic transformation, the structure of employment also changed. Thus, as labor migrates away from agriculture, the productivity, for those who remain in the land, needs to increase significantly. This report examines the constraints to promoting more rapid agricultural, and rural non-farm sector growth, and, reviews the recent performance of the agricultural, and rural non-farm sectors, in particular the non-plantation agricultural sector; scrutinizes the major policy, and regulatory barriers, that hinder a sustained growth in rural areas; and, proposes options for improvement in the key areas. A critical step to achieve this sector growth, and meet the changing demands of the overall economy, is the need to formulate, and implement a renewed rural development strategy, that builds on synergies in the agricultural, and non-farm sectors. This integrated rural development framework becomes an instrument that can complement a sustained growth in the non-farm sector, namely through the performance of public agricultural research, and extension systems, formulated under an updated National Agricultural Strategy and Policy, that modernizes technology policies, and regulations, commits to stabilizing tariff policies, and similarly, commits to implementing policy reforms in land administration, water, labor, commodity marketing, and the commercial private sector. Nonetheless, the report further suggests that prior to implementing this strategy, the Government should formulate a Poverty Reduction Strategy, a critical vehicle for completing the rural strategy framework.